Enhancing community creativity through training on making artificial flowers from plastic waste - Tiara Derawati; Syifaul Fuada (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2021)
The COVID-19 pandemic has a substantial impact on the community, one of which is in the economic sector. Many workers have been laid off, leading to a rise in the unemployment rate in Indonesia. This community service activity aims to help people affected by layoffs as the result of the COVID-19 pandemic through the activities of providing and strengthening functional skills to the community. This online program is a form of the Thematic Community Service Program on Prevention and Countermeasure of The COVID-19 Impact. An artificial flower-making training program has been implemented from plastic waste into a work that can increase people's creativity and grow the community's economy. This artificial flower-making training program's target is based on plastic waste in the community from RT/ RW 01/01, Bojong Village, Majalaya, Bandung District, West Java Province. This program was attended by eight people conducted online through WhatsApp Group from December 1 to 10, 2020. In addition to helping the community increase creativity during the COVID-19 pandemic, creating economically valuable communities can indirectly reduce plastic waste in landfills because plastic waste cannot decompose naturally. People who follow this program can sell artificial flowers to improve the economy during the COVID-19 pandemic.